Conflicts facing Islamic banking in Malaysia: Dual banking system versus dual legal system - Ibrahim, Uzaimah; Muneeza, Aishath; Hassan, Rusni (INSI Publications, 2012)
Islamic banking is everywhere in the world today. But Malaysia is still considered as the leader and cranium of Islamic banking as it has succeeded in creating a full fledge Islamic banking system parallel to the existing conventional system irrespective of the challenges it faced. Today, the new Central Bank of Malaysia Act 2009 has openly declared this reality to the world. Section 27 of the new Central Bank of Malaysia Actstates that Malaysia has dual financial systems that works in parallel that are conventional and Islamic financial system.The adoption of dual banking system is, however been perceived as creating the room for possible legal conflicts. The possible legal conflicts may be due to the fact that the law applicable to Islamic banking is not totally derived from Islamic law and the judiciary system of the country is complex as the court that hears Islamic banking matters are Civil Courts. This paper aims to unravel the reasons or cause of obstaclesin Islamic banking in the Malaysian dual banking structure. This research is novel as few literatures are found on the reason for the cause of conflicts even after the establishing and sustaining Islamic banking in the country for nearly three decades.This is a legal exploratory study primarily focused on library research.